Emission of airborne ultrafine particles during welding of steel plates - Gomes, João (2015)
The present study is focused on the characterization of ultrafine particles emitted in welding of steel using mixtures of Ar+CO2, and intends to analyze which are the main process parameters which may have influence on the emission itself. It was found that the amount of emitted ultrafine particles (measured by particle number and alveolar deposited surface area) are clearly dependent from the distance to the welding front and also from the main welding parameters, namely the current intensity and heat input in the welding process. The emission of airborne ultrafine particles seem to increase with the current intensity as fume formation rate does. When comparing the tested gas mixtures, higher emissions are observed for more oxidant mixtures, that is, mixtures with higher CO2 content, which result in higher arc stability. The later mixtures originate higher concentrations of ultrafine particles (as measured by number of particles by cm3 of air) and higher values of alveolar deposited surface area of particles, thus resulting in a more hazardous condition regarding worker's exposure. © 2014 Sociedade Portuguesa de Materiais (SPM). Published by Elsevier España, S.L. All rights reserved.